Photonic multipartite entanglement in discrete variables without arbitrary unitaries - Milica Banić; J. E. Sipe; Marco Liscidini (Physical Review Research)
We present an approach for designing sources of postselected multipartite states based on photon-pair sources. Our approach can be applied to arbitrary target states in different encoding schemes and physical platforms. It also allows one to limit the types of components to be used in the device, such that lossy or difficult-to-implement optical elements can be avoided. As an example, we apply this strategy to design a passive integrated source of frequency-bin-encoded high-dimensional GHZ states with a 10-kHz on-chip generation rate for picojoule pump pulses.